2009
DOI: 10.2136/vzj2008.0011
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Gas Transport Parameters in Unsaturated Silica Flour

Abstract: A: DGM, Dusty Gas Model.T N An experimental study was conducted to assess the rela ve contribu ons of molecular and Knudsen diff usions for gasphase transport in unsaturated silica fl our with an intrinsic permeability of 1 ? 2 × 10 −14 m 2 . Single-gas phase fl ow and binary diff usion experiments were performed on the same soils to determine the Knudsen diff usion and the eff ec ve gas-phase diff usion coeffi cients, respec vely. These results were further used to assess the diff usibility factor for Fick's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Taking into account that diffusion capacity is related to impedance to gas diffusion, which depends on the shape and orientation of the soil pores (Fen et al, 2009), it can be also suggested that this pore arrangement, plus a WFPS percentage close to 90 %, could reduce the rate at which gases move from the soil to the atmosphere (Glinski & Stepniewski, 1985). This is consistent with results of Bartelt-Hunt & Smith (2002), who found that with a decrease in soil moisture content, and therefore an increase in the percentage of air-filled pores (30 to 39 %), the gas diffusion coefficient rises from 0.0133 to 0.0609 cm 2 s -1 .…”
Section: Resultsmentioning
confidence: 99%
“…Taking into account that diffusion capacity is related to impedance to gas diffusion, which depends on the shape and orientation of the soil pores (Fen et al, 2009), it can be also suggested that this pore arrangement, plus a WFPS percentage close to 90 %, could reduce the rate at which gases move from the soil to the atmosphere (Glinski & Stepniewski, 1985). This is consistent with results of Bartelt-Hunt & Smith (2002), who found that with a decrease in soil moisture content, and therefore an increase in the percentage of air-filled pores (30 to 39 %), the gas diffusion coefficient rises from 0.0133 to 0.0609 cm 2 s -1 .…”
Section: Resultsmentioning
confidence: 99%
“…Note that the experimental results for the samples DSF 1 and DSF2, and WSFl, WSF2, and WSF3 were presented in Fen et al (2009) and are also provided here for discussion. Table 2 presents the apparent permeability values for each sample determined by Eq.…”
Section: Methodsmentioning
confidence: 99%
“…They found that the predictions obtained from this correlation wete less than the results from the difftisivity models of Millington and Qiiirk (1961), Penman (1940), Gurrie (1970), Lai et al (1976), and Millington and Shearer (1970). Fen et al (2009) obtained another correlation of the obstruction factor for silica Hour at various water saturations and with effective gas permeabilities ranging from 10"^'^ to 10"'^ m^. Their predictions of this correlation were far less than the result obtained from the diffusivity models of Millington and Qmrk (1961) and Moldrup et al (2000).…”
mentioning
confidence: 89%
See 2 more Smart Citations